DEVELOPMENT OF PROJECT BASED WORKSHEETS ON THE UTILIZATION OF FERMENTED DATE SEEDS WASTE AS A RAW MATERIAL TO DRINKING DATE COFFEE - Rifa Zaena Tazqiyah; Neneng Windayani; Imelda Helsy (Gunung Djati Conference Series, 2021)
This study aims to describe the appearance of project-based worksheet products and to analyze the results of project-based worksheet validation tests on the utilization of fermented date palm waste as raw material for date coffee drinks. This research method is Design Based Research (DBR), with three stages, namely analysis, design, development. These stages include analysis of fermentation chemicals, analysis of literature on the content of date seeds, literature analysis of fermented coffee processing research, analysis of steps on project-based worksheets and then linking experimental procedure design to developing project-based worksheets. The instrument used was a validation test questionnaire using the correlation technique (r). The results of this research are in the form of a project-based worksheet product on the use of fermented date coffee waste as raw material for date coffee drinks, with a validation test result of a mean count of 0.87. Thus the resulting project-based worksheets are declared valid and worthy of being used as learning media.